Associations of Endogenous Estradiol and Testosterone Levels With Plaque Composition and Risk of Stroke in Subjects With Carotid Atherosclerosis. Issue 1 (5th January 2018) - Glisic, Marija; Mujaj, Blerim; Rueda-Ochoa, Oscar L.; Asllanaj, Eralda; Laven, Joop S.E.; Kavousi, Maryam; Ikram, M. Kamran; Vernooij, Meike W.; Ikram, M. Arfan; Franco, Oscar H.; Bos, Daniel; Muka, Taulant
Abstract : Rationale: : Sex steroids may play a role in plaque composition and in stroke incidence. Objectives: : To study the associations of endogenous estradiol and testosterone with carotid plaque composition in elderly men and postmenopausal women with carotid atherosclerosis, as well as with risk of stroke in this population. Methods and Results: : Data of 1023 postmenopausal women and 1124 men (≥45 years) with carotid atherosclerosis, from prospective population-based RS (Rotterdam Study), were available. At baseline, total estradiol (TE) and total testosterone (TT) were measured. Carotid atherosclerosis was assessed by ultrasound, whereas plaque composition (presence of calcification, lipid core, and intraplaque hemorrhage) was assessed by magnetic resonance imaging. TE and TT were not associated with calcified carotid plaques in either sex. TE was associated with presence of lipid core in both sexes (in women odds ratio, 1.48 [95% confidence interval [CI], 1.02–2.15]; in men odds ratio, 1.23 [95% CI, 1.03–1.46]), whereas no association was found between TT and lipid core in either sex. Higher TE (odds ratio, 1.58 [95% CI, 1.03–2.40]) and lower TT (odds ratio, 0.82 [95% CI, 0.68–0.98]) were associated with intraplaque hemorrhage in women but not in men. In women, TE was associated with increased risk of stroke (hazard ratio, 1.98 [95% CI, 1.01–3.88]), whereas no association was found in men. TT was not associated with risk of stroke in either sex. Conclusions: : TE was associated with presence of vulnerable carotid plaque as well as increased risk of stroke in women, whereas no consistent associations were found for TT in either sex. Abstract : Supplemental Digital Content is available in the text.